Tanggung Jawab Hukum Notaris Pengganti terhadap Akta yang Dibuatnya yang Mengandung Cacat Formil dan Cacat Materiil - Yolanda Putriane (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to examine how the authority of a substitute notary in making authentic deeds is regulated according to the provisions of laws and regulations in the field of notarial affairs and what form of legal responsibility the substitute notary takes for the deeds they make if they contain formal and material defects. This type of research is normative legal research using a statutory approach, a conceptual approach and a case approach. The results of this study indicate that the authority of the Substitute Notary is regulated in laws and regulations that provide the same status and authority as a Notary in making authentic deeds, as long as they meet the applicable terms and conditions. The legal responsibility of the Substitute Notary for the deeds they make remains attached to him personally, both civilly, administratively and criminally if a violation is proven. Formal defects in the deed can cause the deed to lose its authentic nature and only have the force as a private deed, while material defects can have implications for the cancellation or annulment of the deed. Therefore, the Substitute Notary is required to carry out his duties carefully, thoroughly and in accordance with applicable legal provisions to avoid legal risks in the future.